(3LRA GdOjHGLs
(3ChdgG (B:s
(3eMeO Hf GSeGYjd GdHNGQi MOKfG hSYjO Hf CHj eQje MOKfG eMeO Hf LYaQ GNHQfi MejO GHf CHj MejO Gfg SeY GfS Hf eGdc bGd (B( (3LGA KdGKI QgW Edi HjJ GRhGL GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hQLd dGjOQi hdGjOQi Gfg dGjOQi aPGc LGgd aGQaVhg BNQ GdLRA GdChd s
(3GdfSNI HgG MhGTs
(3HBNQg JUMjMGJs
(3Ydjg NW GdMGaX YeQ Hf eMeO Hf eYeQ Hf jMji Hf WeGO GdHZOGOi SfI (B604(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs